How Online Information Sources Affect Law Enforcement Perceptions - Benson, David C. (International Journal of Police Science, 2022)
The internet is a part of daily life, but the law enforcement community is still struggling to adapt policing research and practice to the internet due to a limited understanding of the various online information sources affecting law enforcement and security. This article addresses information as a function of policing or crime and focuses on how online sources of information may be used to prepare for, commit, prevent, investigate, and prosecute crimes.